Bigadiç'te 45-74 yaş bireylerde diyabet prevalansı ve farkındalık durumunun belirleyicileri/Determinants of prevelance and awareness of diabetes in a population aged 45-74 in Bigadic - Kevser Tarı Selçuk; Belgin Ünal (Turkish Society of Public Health Specialists, 2013)
Özet Amaç: Bu kesitsel araştırmada Bigadiç ilçe merkezinde yaşayan 45-74 yaş bireylerde diyabet prevalansı ve farkındalık durumunun saptanması, diyabet prevalansı ve farkındalık durumunu etkileyen etmenlerin belirlenmesi amaçlanmaktadır. Yöntem: Araştırma grubu 45-74 yaş 4.425 kişiden küme örnekleme yöntemiyle seçilen 509 kişiden oluşmaktadır. Araştırmanın bağımlı değişkenleri diyabet varlığı ve diyabet farkındalık durumudur. Araştırmada diyabet tanısı için random kapiller kan glukoz, Glikozillenmiş Hemoglobin (HbA1c) ölçümleri yapılmış, değerlendirmede Amerikan Diyabet Birliği (ADA) 2010 yılı tanı kriterleri kullanılmıştır. Çözümlemede tanımlayıcı istatistikler, ki kare, lojistik regresyon analizi kullanılmıştır. Araştırmanın bütçesi Dokuz Eylül Üniversitesi Bilimsel Araştırma Projeleri tarafından desteklenmiştir (Proje no: 201194). Bulgular: Araştırma grubunda diyabet prevalansı %21.0, diyabet farkındalık oranı %66.3'tür. Diyabet farkındalık oranı yalnızca yaşla ilişkili bulunmuştur; farkındalık 60 yaş ve üzerindekilerde daha yüksektir (p=0.039). Lojistik regresyon analizinde diyabet prevalansı 60 yaş ve üzerindekilerde [OR=1.86, %95 GA:1.11-3.15], eşlik eden kronik hastalığı olanlarda [OR= 2.65, %95 GA:1.54-4.56], fazla kilolularda [OR=4.56, %95 GA:2.11-9.58] ve obezlerde [OR=2.64, %95 GA:1.51-4.63] istatistiksel olarak anlamlı düzeyde yüksektir. Sonuç: Yetişkinlerde diyabetin önlenmesi amacıyla topluma yönelik birincil koruma önlemleri olan obezitenin azaltılması, fiziksel aktivitenin artırılması önlemlerine ağırlık verilmelidir. Diyabetli bireylerde komplikasyonların önlenmesi amacıyla birinci basamak sağlık kuruluşlarında düzenli izlem programları oluşturulmalı, farkındalık düzeyini arttıracak bilgilendirmeler ve fırsatçı taramalar gibi girişimler planlanmalı ve uygulanmalıdır. Anahtar Kelimeler: Diyabet, prevalans, farkındalık Determinants of prevelance and awareness of diabetes in a population aged 45-74 in Bigadic Abstract Objective: The aim of this cross-sectional study was to determine the prevelance and awareness of diabetes and to evaluate associated factors in a population aged 45 to74 in Bigadic. Method: The study group included 509 subjects selected from 4.425 individuals aged 45-74 years using the cluster sampling method. The dependent variables of the study were the existence and awareness of diabetes. The proportion of people with a history of diabetes relative to the total number of individuals with diabetes gives the diabetes awareness ratio. Diabetes was defined according to American diabets Association (ADA) diagnosis criteria for the year 2010 and is based on random capillary blood glucose and HbA1c levels. The chi-square test and logistic regression analysis were used to evaluate the associations with independent variables. The study was financially supported by Dokuz Eylül University Scientific Research Projects (Project no: 201194). Results: The prevelance of diabetes was 21.0% and 66.3% of individuals were aware of their condition. Diabetes prevelance was associated with age, sex, marital status, education, employment, family type, comorbidity, BMI and blood pressure (p<0.05). Awareness of diabetes was higher in the over 60 age group (p=0.039) than in the younger group. In a logistic regression analyses the prevelance of diabetes was higher in those aged 60 and above [OR=1.86, 95% CI:1.11-3.15], who had comorbidity [OR=2.65, 95% CI:1.54-4.56], who were overweight [OR=4.56, 95% CI:2.11-9.58] or obese [OR=2.64, 95% CI:1.51-4.63]. Conclusion: In order to prevent diabetes in adults primary preventative interventions leading to increased physical activity and decreased obesity in the population should be considered. Regular monitoring programs should be developed as a part of primary health care for diabetes patients to prevent complications. Health education and screening programs should be used to increase the level of awareness in people with diabetes. Key Words: Diabetes, prevalance, awareness